Estudo comparativo da Hymenopterofauna detritívora de duas unidades fisiográficas da Restinga da Marambaia (Baía de Sepetiba, Rio de Janeiro, RJ) - Xerez, Roberto de (1992)
The role of the detritivorous arthropofauna on the nutrient recycling on the Neotropical region has been poorly studied. The objective of this study was to estabish the participation parcel of the most abundant group of this detritivorous on two physiographic regions of Marambaia, Rio de Janeiro, RJ. Because it still maintains a representative portion of Coastal rain forest, the Marambaia island proved to be an excellent place for this study. ln both regions the forest region (PG) and the salt marsh (PA) were installed two type NTP-80 traps, containing baits made of fish and chicken grounded meat, respectivelly. Monthly the contains were colleceted and analysed. The composition of the entomofauna detritivorous, included 16 taxa, being the hymenopterans the most abundant group, representing more than 52% of the total individuals co11ected. The number of hymenopterans presented im PG was signicantly greater than the one in PA, opposite1y the greatest diversity ( H') was found in the salt marsh . ln both environment the total number of hymenopterans on the fish bait was greater than in the chicken bait; oppositely to the greater diversity that was found in the chicken bait on both areas. It was found nearly 50% similarity between the detritivorous hymenopteran fauna composition in the forest and in the salt marsh area.